Late diagnosis of isolated central diabetes insipidus secondary to congenital toxoplasmosis—case report. Issue 11 (24th November 2020) - Omer, Tahir; Khan, Mustafa; Western, Thomas
ABSTRACT: Congenital toxoplasmosis is an uncommon infection. Hypothalamic/pituitary involvement leading to isolated central diabetes insipidus is extremely rare. Making a correct diagnosis of this condition, albeit challenging, is crucial for adequate management. We present a 54-year-old female who developed central diabetes insipidus as a complication of congenital toxoplasmosis. She had polydipsia and hypernatraemia on presentation and responded to intranasal desmopressin with normalization of above-mentioned findings. Magnetic resonance imaging and cranial X-ray's showed pronounced intracranial calcifications in both choroid plexuses. Thyroid function tests, serum cortisol level and anterior pituitary function were all normal. To the best of our knowledge, this is the first reported case of isolated diabetes insipidus due to congenital toxoplasmosis in literature diagnosed late in adulthood and gives an insight into the challenges of diagnosing central diabetes insipidus and the hypothalamic/pituitary involvement in cases of congenital toxoplasmosis.